PERTANGGUNGJAWABAN PIDANA BAGI PENGEMUDI DALAM KECELAKAAN LALU LINTAS DI WILAYAH HUKUM POLRES KUTAI TIMUR - nanang santoso (Journal of Law ( Jurnal Ilmu Hukum ), 2015)
Abstract This study was conducted to determine how the criminal liability driver of the vehicle involved a traffic accident that resulted in the death of others. To know and analyze on the driver's obligation to provide compensation to the victims. Criminal responsibility of the driver's vehicle resulting in death in a traffic accident in Article 359 of the Book of Law OF criminal law is imprisonment of five years or a maximum imprisonment of one year, may also be given criminal sanctions as set in Article 310 of Law number 22 Year 2009 regarding Traffic and Road Transportation.